The Fertility Effects of School Entry Decisions - Rebecca Kamb; Marcus Tamm (Institute of Labor Economics (IZA), 2021)
School entry regulations lead to differences in the age when children start school. While previous literature estimated the effects of age at school entry for compliers with school entry regulations, we look at non-compliers, namely those who enter school one year before the official entry date. Based on an instrumental variable approach, the results show that early enrollment increases the number of children by 0.1, whereas we find no significant impact on rates of childlessness.
Keywords: I21; J24; 330; school starting age; early school enrollment; fertility; motherhood; childlessness